Effect of the level of coordinated motor abilities on performance in junior judokas - Lech, G.; Jaworski, J.; Lyakh, V.; Krawczyk, R. (Journal of Human Kinetics, 2011)
The main focus of this study was to identify coordinated motor abilities that affect fighting methods and performance in junior judokas. Subjects were selected for the study in consideration of their age, competition experience, body mass and prior sports level. Subjects' competition history was taken into consideration when analysing the effectiveness of current fight actions, and individual sports level was determined with consideration to rank in the analysed competitions. The study sought to determine the level of coordinated motor abilities of competitors. The scope of this analysis covered the following aspects: kinaesthetic differentiation, movement frequency, simple and selective reaction time (evoked by a visual or auditory stimulus), spatial orientation, visual-motor coordination, rhythmization, speed, accuracy and precision of movements and the ability to adapt movements and balance. A set of computer tests was employed for the analysis of all of the coordination abilities, while balance examinations were based on the Flamingo Balance Test. Finally, all relationships were determined based on the Spearman`s rank correlation coefficient. It was observed that the activity of the contestants during the fight correlated with the ability to differentiate movements and speed, accuracy and precision of movement, whereas the achievement level during competition was connected with reaction time.